The sorcerer's apprentice - Chandler, Fiona; Bernatene, Poly (London : Usborne ; Tulsa, Okla. : EDC, 2007)
Illustrations and simple text tell the classic story "The Sorcerer's Apprentice" about a boy named Max who is learning to be a sorcerer and runs into trouble when he tries to do some magic on his own.
2.9
K-3
Keywords: Magic -- Fiction; Fantasy; Apprentices -- Fiction; Magic -- Fiction; Fantasy fiction; Apprentices -- Fiction